Multi-dimensional human interaction in open spaces for Shah Alam City, Selangor, Malaysia / Filzani Illia Ibrahim - Ibrahim, Filzani Illia (Institute of Graduate Studies, 2017)
Due to rapid urban development, open spaces have changed drastically over the decades and generations have been struggling with its consequences. There are various studies on how open spaces provide positive reaction to human. Apparently, in relation to open spaces, Malaysia has received very little attention from researchers. Given this scenario, this study investigates the human interaction experienced in the open spaces and how it relates to the city sustainability. The aim of this research is to evaluate the multi-dimensional human interaction experienced in the open spaces and develop the ranking of human interaction in relation to the typological of open spaces. The analysis in this study addresses human-human interaction and human-nature interaction in five selected open spaces of Shah Alam, Selangor, Malaysia namely Section 2 Urban Park, Section 7 Local Park, Section 18 Neighbourhood Park, Section 8 Playing Field, and Section 4 Playground. This research adopted mixed methodology after taking into consideration the nature of the research topic, structure and composition of the population, the type of information sought and the availability of the resource. In this research, a mixed methodology is employed using a combination of questionnaire surveys, semi-structured interviews, multiple case studies and behaviour mapping. For the questionnaire survey, the stratified random sampling ...